Appropriate number of stages of an ORC driven by LNG cold energy to produce acceptable power with reasonable surface area of heat exchangers. (December 2022) - Joy, Jubil; Chowdhury, Kanchan
Highlights: Two-stage ORC with first stage cascaded is most suited for practical implementation. It is the best compromise among power generation, complexity and heat exchanger UA. Power output increases as total UA is appropriately allocated to the heat exchangers. The best configuration sacrifices only 8.6% power compared to 3-stage cascaded one. Heat exchanger UA in the best configuration is 20% lower than 3-stage cascaded one. Abstract: Cold energy of LNG can generate power through Organic Rankine cycle (ORC). Although power output increases with number of stages, they become complex, expensive, maintenance-intensive and prone to failure due to the presence of increased number of components. In this paper, a cascaded three-stage ORC system has been progressively truncated finally to a single-stage system to arrive at the appropriate trade-off between the plant complexity and generation of power. Sea-water is used as the heat source and with ethene, ethane and propane as the working fluids, the generation of power is maximised for a given total surface area of heat exchangers. Calculation has been done initially with 5 K temperature approach in all the heat exchangers. However, an appropriate distribution of total surface area times overall heat transfer (UA) resulting in an unequal temperature approaches in the heat exchangers generated much higher output of power. The simulation shows that though cascaded three-stages delivers the highest power. A two-stage system with only the first stage cascaded reduces power generation by 8.6% compared to that in a three-stage system. However, the former gains enormously in simplicity of configuration and operation. The corresponding reduction in surface area of the heat exchanger is 20%.